Peningkatan Aktivitas Belajar Dan Hasil Belajar Siswa Pada Materi Hak Asasi Manusia Dalam Terang Kitab Suci Dan Ajaran Gereja Dengan Model Problem Based Learning (PBL) Pada Siswa Kelas XI Saint John Catholic School - Hermanus Agun (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Good education is the main foundation for the progress of a nation. In the era of globalization and intensified competition, the good education is the key to prepare the young generation to face the challenges of the future. Through the good education, young people are given the opportunity to develop their creative thinking, problem-solving and technological skills needed in the face of a rapidly changing world. Furthermore, good education is also an important pillar in a democratic system. Young people who receive a good education tend to have the ability to think critically, analyzing information, and participate actively in the political process. Recognising the importance of education, the Indonesian nation pays much more attention to the issue of education, even the objectives are increasingly refined. This is in accordance with the provisions contained in the preamble of the 1945 Constitution. Broadly speaking, education is an effort to educate the nation's life in order to become a whole human being with the spirit of Pancasila. The Law of the Republic of Indonesia No. 20 of 2003 on the National Education System also states as follows: "National education functions to develop abilities and form the character and civilisation of a dignified nation in order to educate the nation's life, aims to develop the potential of students to become human beings who are faithful and devoted to God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens". Realising how important the value of education is for human life, the researcher feels called to conduct research on educational issues that occur in the school where the researcher works as an educator, namely Saint John Catholic High School, BSD. This research was conducted to determine the extent to which the Problem-Based Learning (PBL) model has an impact on the learning process at Saint John Catholic School High School both in activity and student learning outcomes. This process will be conducted in two stages, namely cycle I and cycle II. In each cycle there will be four steps: action planning, action implementation, observation and reflection. The implementation of cycle I ended with a reflection that showed that student activity and student learning outcomes had not yet achieved results in accordance with the minimum standards set. The reflection carried out in cycle I is the basis for evaluation for improvement in the action process in cycle II. In the process of class action in cycle II, the results were known to be very good, thus the action process stopped in cycle II. The satisfactory results in cycle II are the basis for making the conclusion that the application of problem-based learning models is very suitable for improving learning activities and learning outcomes of Saint John Catholic School grade XI students.